Brand valuation study of two coffee shops located in Guayaquil - Norero, Giovanni; Loor Rosales, Joffre Bernardo (Revista Universidad de Guayaquil, 2018)
Companies use several types of indicators to measure their financial performance in relation to costs, production and sales but many do not pay due attention to one of the most important assets they have: the brand. The brand is the figure, whether iconic or font, which belongs to the intangible assets of companies whose principal objective is to make the customer associate a service or product to its manufacturer. In the Ecuadorian market, companies have brands but none of them have real monetary value. This study assessed the value of two brands but not from the subjective or emotional point of view that consumers may give to them but from the monetary value. To achieve this, two brands were considered: one was a traditional coffee shop in the city of Guayaquil operating for over 100 years and it was contrasted with the market leader. Sale records generated over three years for each of the companies were used and the Interbrand valuation method was applied to obtain the brand values showing that the brand belonging to the market leader is worth 11 million dollars more than the one of the traditional coffee shop.